Mapping multilevel barriers impacting the performance of Ethiopia’s Community-Based Health Extension Program: A scoping review - Kora Tushune Godana; Zewdie Birhanu; Gugsa Nemera; Kasahun Eba; Fikadu Balcha; Yibeltal Assefa; Wim V. Damme; Peter Decat (PLoS ONE, 2026)
Background Ethiopia’s Health Extension Program (HEP) aims to improve primary care access through community-based delivery of essential preventive and promotive services. Despite progress, some health outcomes remain suboptimal, underscoring the need to optimize HEP implementation. Identifying barriers of the HEP and its Health Extension Workers (HEWs) is critical for enhancing program effectiveness. This scoping review aims to identify and synthesize evidence on the barriers impacting the performance of the Ethiopian HEP and HEWs. Methods A comprehensive search strategy was conducted across multiple databases, including PubMed, EMBASE, Web of Science, and relevant institutional websites, as well as hand searches via Google Scholar and Google engine, to identify both published and unpublished documents (documents (government reports and policy documents (strategic plans, program reviews, annual performance reports), development partner publications, doctoral dissertations, and masters theses) related to the HEP. The review encompassed studies published since January 2003. Data extraction was performed using Atlas.ti software version 7.5.18, which facilitated the collection of verbatim excerpts and the application of thematic coding to highlight key findings. The results are organized and presented through thematic analysis, focusing on multi-dimensional barriers and challenges. Results The review reveals multi-dimensional barriers, including a misalignment between the HEP’s preventive design and the community’s demand for curative services, which undermines community trust and program acceptance, and gender-imbalanced workforce, which creates barriers to service delivery in certain cultural contexts. Additional barriers include a lack of training and retention strategies, and digital literacy and access gaps which further impede effectiveness of the program. Excessive workloads, non-health tasks, and poor living conditions, divert HEW’s focus from their primary responsibilities. Weak community engagement, inadequate integration of Traditional Birth Attendants (TBAs), and inefficiencies in model family development limit the program’s impact. Misconceptions in the community, resource constraints, fragmented stakeholder interactions, ineffective supervision, governance issues, and political interference directly impede performance. Conclusion The HEP faces deeply entrenched, multi-dimensional barriers that limit its potential to achieve optimal health outcomes. Key policy recommendations include integrating curative services, ensuring a balanced gender mix in the workforce, improving working conditions and expanding community engagement. Further research is needed to quantify barriers, assess their impact, and identify key influencing factors, with stakeholder engagement and implementation research being essential for developing effective solutions.